2019
DOI: 10.3892/ol.2019.10420
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism changes during the development and progression of oral tongue squamous cell carcinomas

Abstract: Previous studies have revealed several genes involved in the carcinogenesis of oral cancer. However, the detailed mechanisms underlying this process are poorly understood. Previously, we established a database cataloging the transcriptional progression profile of oral carcinogenesis and identified several candidate genes with continuously increasing or decreasing expression, which specifically promote the transition of oral premalignant lesions to invasive carcinomas. In this study, using our microarray databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…It has been demonstrated that glycolysis metabolism was associated with tumor cell development and progression in oral tongue squamous cell carcinomas (38). In the results of the present study, regardless of whether PD-L1 was overexpressed or knocked-down, the expression of HK2 and LDHA was increased or decreased in AML cells MOLM-13 with cell proliferation altered, which was consistent with the results observed in other tumor types (38). Several studies have reported the impact of glycolysis in AML.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been demonstrated that glycolysis metabolism was associated with tumor cell development and progression in oral tongue squamous cell carcinomas (38). In the results of the present study, regardless of whether PD-L1 was overexpressed or knocked-down, the expression of HK2 and LDHA was increased or decreased in AML cells MOLM-13 with cell proliferation altered, which was consistent with the results observed in other tumor types (38). Several studies have reported the impact of glycolysis in AML.…”
Section: Discussionsupporting
confidence: 92%
“…Targeting HK2 with costunolide decreased the uptake of glucose and lactate accumulation, resulting in suppression of hepatic stellate cell viability, which is the major cell for hepatic fibrosis (37). It has been demonstrated that glycolysis metabolism was associated with tumor cell development and progression in oral tongue squamous cell carcinomas (38). In the results of the present study, regardless of whether PD-L1 was overexpressed or knocked-down, the expression of HK2 and LDHA was increased or decreased in AML cells MOLM-13 with cell proliferation altered, which was consistent with the results observed in other tumor types (38).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the malignant phenotype of most tumor tissues is closely related to the metabolisms of special material and energy, such as oral cancer (Nakazato et al 2019), hepatocellular carcinoma (Fang et al 2019), pancreatic cancer (Yang et al 2019), non-small cell lung cancer (Zhang et al 2019), prostate cancer (Marin de Mas et al 2019), etc. Colorectal cancer (CRC) is the most frequent malignant gastrointestinal tumor and a leading cause of cancer death worldwide, along with an increase of about 150,000 cases every year (Jemal et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high GLUT1 expression was found in the advanced non-papillary type and larger tumor sizes of CCA. The increasing expression of GLUT1 during progression of cancer may be an essential characteristic of cancer as this event was also observed in many types of cancer, such as cervical cancer (23), hepatoma (24), and oral tongue squamous cell carcinomas (25).…”
Section: Discussionmentioning
confidence: 92%